Application of GO Management in Bistatic RCS Computation Using the Vector Parabolic Equation Method - X. J. Zhong; T. J. Cui; J. F. Zhang; W. M. Yu (International Journal of Antennas and Propagation)
The parabolic equation (PE) method is a good choice in solving large-scale problems, but the resultant matrix is usually ill conditioned. In this letter, we introduce the geometric optics (GO) management in the calculation of bistatic radar cross sections using three-dimensional vector PE method. This method manages the object surface by GO, and hence the ill-conditioned problem can be avoided. Examples are given using the presented method, original method, and the method of moments. Results show the validity and stability of the presented method.